A Multi-Domain Intervention Protocol for the Potential Reversal of Cognitive Frailty: “WE-RISE” Randomized Controlled Trial - Murukesu, Resshaya Roobini; Singh, Devinder Kaur Ajit; Shahar, Suzana; Subramaniam, Ponnusamy (Frontiers in Public Health, 2020)
Following the rapid increase of the aging population, health promotion and prevention of physical disability and dementia in older persons are essential for healthy aging. For example, there may be a potential to prevent or reverse cognitive frailty, the co-existence of both physical frailty and cognitive impairment in older persons. However, evidence-based interventions targeting the prevention or potential reversibility of cognitive frailty among community dwelling older adults are scarce. In this paper, we described the rationale, development and delivery of a multi-domain intervention comprising multi-component physical exercise prescription, cognitive training, dietary counseling and promotion of psychosocial support, called the WE-RISE trial. The aim of WE-RISE intervention is to potentially reverse cognitive frailty. This is a two-armed, single blinded, randomized controlled trial conducted over a duration of 6 months, at senior citizen activity centers within the Klang Valley, Malaysia. Ambulating, community dwelling older adults aged 60 years and above with cognitive frailty are randomized into two groups; (1) intervention group: which receives an instructor based “WE-RISE” intervention for the first 3 months, and then a home-based “WE-RISE at Home” intervention for the following 3 months; (2) control group: usual care with no modifications to their daily routine. Primary outcome is cognitive frailty status and secondary outcome include physical function, cognitive performance, nutritional status, psychosocial status and quality of life which are obtained during baseline screening and subsequent follow ups at 3rd and 6th month. Description of the intervention is done using the template for intervention description and replication (TIDieR) checklist. This trial protocol has received approval from Research Ethics Committee of Universiti Kebangsaan Malaysia (UKM PPI/111/8/JEP-2018-558) and the Department of Social Welfare Malaysia (MyResearch Reference: JKMM 100/12/5/2: 2018/405). Trial registration number: ACTRN12619001055190.